A noninvasive tonometer in the measurement of the effects of pindolol and timolol on intraocular pressure in normal subjects. Issue 8 (August 1981) - Rowley, S.; Staunton, J. E.; Tosch, A.; Stewart-Jones, J. H.; Edgar, D. F.; Turner, P.
Abstract : A noncontact tonometer was used to demonstrate in normal human volunteers the ocular hypotensive effects of single instillations of pindolol (1%) and timolol (0.25 and 0.5%) eye drops. Falls in intraocular pressure were significantly correlated with resting intraocular pressure. Evidence of systemic cardiovascular effects was seen in reductions in resting heart rate.